HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN PEMBERIAN IMUNISASI TETANUS TOKSOID DI WILAYAH KERJA PUSKESMAS MAGA KECAMATAN LEMBAH SORIK MARAPI KABUPATEN MANDAILING NATAL TAHUN 2015 - eskalila suryati; Asfriyati .; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
ABSTRACT Tetanus is primary cause of maternal and neonatal mortality .The coverage of TT immunization in Health centers Maga sub district of Lembah Sorik Marapi is lower. In 2014,of the 210 pregnant women, TT1 immunization coverage was 34(16,2%) and TT2’s was 25 (11,9%) This study aims to determine the relationship between knowledge and attitude with Tetanus Toxoid Immunization in the sub district Health centers Maga Lembah Sorik Marapi, Mandailing Natal. This type of this research is observational study with cross-sectional design. Samples based on total sampling are all pregnant women with gestational age more than 8 months in the working area health centers Maga as many as 42 people. Analysis of data using chi-square statistical test using 95% confident level (α=0,05) The result showed that there was a correlation between knowledge (p=0,027) and attitude (p=0,008)of pregnant women with TT immunization for pregnant women in sub-district Health centers Maga Lembah Sorik Marapi Mandailing Natal. Public health center is expected to boost the function of promotion to increase public knowledge about TT immunization and improve health service so as to improve immunization coverage. Keywords: knowledge, attitude, pregnant woman, TT immunization